Sciatica - Ever Suffered an Agony - Intervention with Homoeopathy (Homoeopathy for All, 2023)
Ever suffered a gnawing pain called sciatica? Sciatica pain is pretty clear cut, piercing or shooting pain in the lower back, which radiates down buttocks and legs. It is more common in men than women. Homoeopathy is considered as one of the very best alternative systems for treating Sciatica pain. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this gnawing pain.
Keywords: piercing or shooting; gnawing pain; diagnosis